Pemberdayaan Masyarakat dalam Pengelolaan Lingkungan yang Berkelanjutan di Kota Padang - Fariska Wina Utari Alwi; Hazella Vioma Rizka; Maulani Azizah; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Environmental management represents a critical issue faced in the development of urban areas, including in the city of Padang. Environmental management refers to all efforts undertaken to preserve, protect, improve and utilize the environment in a wise and sustainable manner. This rearch seeks to explore the role of community empowerment as a strategic approach to improving environmental management. Furthermore, the study intends to increase public understanding regarding the significance of managing the environment. Through empowerment program, it is expected that the community will not only actively participate but also understand their strategic role in maintaning environmental sustainabillity.This Study employs a literature review method by synthesizing and evaluating a range of prior research concerning,encouraging active involvement and fostering shared responbillity in preserving environmental quality, thereby achieving the goal of creating a clean, healthy and sustainable environment.